Comparison of Glazing Types in Terms of Cost Efficiency and Total Energy Consumption - Iplik, Iril; Tartan, Gulcin Gulsum Konuk; Uyduran, Hizir Gokhan; Ilgurel, Mehmet Nuri (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2026)
Energy efficiency in buildings has become an increasingly important design criterion in the context of sustainable architecture. In this context, building envelope components such as window systems must be thoroughly evaluated in terms of energy performance, initial costs, and long-term total cost. This study draws attention to the limitations of the commonly adopted one-dimensional approaches in selecting window glazing systems and offers a comprehensive analysis across three key parameters: Investment cost, energy consumption, and life cycle cost. A total of 64 scenarios are developed for a theoretical residential building located in Istanbul. Comparisons are made across three key performance criteria, taking into account different facade orientations (north/south) and window-to-wall ratios (30%/60%). The results reveal that the optimal window systems differ across the performance criteria, suggesting that selecting a system based solely on energy consumption or investment cost may result in suboptimal or misleading outcomes. Systems with low energy consumption often come with higher investment costs, which may limit the potential to minimize overall life cycle cost. Double-glazed systems with solar low-e coatings tend to yield more favorable life cycle cost outcomes, thanks to their relatively low investment costs and balanced overall performance. The study underscores the importance of adopting a multidimensional approach in window system selection and offers practical guidance to decision-makers aiming for cost-effective design strategies.
Keywords: Key Life cycle cost; investment cost; glazing types; solar low-e coating; argon filling; LIFE-CYCLE ASSESSMENT; RESIDENTIAL BUILDINGS; DESIGN CRITERIA; WINDOW; PERFORMANCE; ORIENTATION; COATINGS; IMPACTS; AREA; Architecture